The way of the shark : lessons on golf, business and life - Norman, Greg, 1955-; Phillips, Donald T. (Donald Thomas), 1952- (North Sydney, N.S.W. : Random House Australia, 2007)
"Greg Norman is one of the most popular golfers in the sport's history. Now for the first time, and with his trademark charm and eloquence, golf's 'Great White Shark' chronicles his extraordinary life and career, revealing how lessons learned on pressure-packed putting greens prepared him for phenomenal results in the boardroom. A fascinating story, an incredible career and a lifetime of business strategies and secrets for success, Greg Norman: the way of the shark, is an irresistible, inspirational and intriguing portrait of a great Australian character." -- Publisher.
Includes index.
Keywords: Norman, Greg, -- 1955-; Golfers -- Australia -- Biography